GAGASAN FORMASI NALAR ARAB ĀBID AL-JĀBIRĪ DAN SIGNIFIKANSINYA UNTUK REKONSTRUKSI NALAR ACEH - Zulfata Zulfata (Islam Futura, 2016)
Ābid al-Jābirī was an influential figure during his time. His thoughts was delivered through his works which was able to arise the Muslim awareness. This study discusses the ideas of Muhammad Ābid al-Jābirī and what are the affects of his thinking concept. This study is library research with the philosophy historical as an indicator tracing on the problems being discussed. The results show that Ābid al- Jābirī thoughts trying to deconstruct the historical facts happened within the Arab nation. The deconstruction process is analyzed through the Islamic epistemological approach. Although there are some problems were not been resolved by al-Jābirī, but the discourses being lifted could be respond and give new works that continue to discuss relates to the Arab nation criticism historical. His thoughts are also very significant as the efforts to establish the Aceh contemporary civilization.